The internationalization of Malaysian palm oil firms: The role of network relationships / Anuar Md Nor - Md Nor, Anuar (Institute of Graduate Studies, UiTM, 2016)
There have been many studies conducted on multinationals from large developing Asian countries such as China and India. The multinationals from smaller Asian countries, such as Malaysia, Thailand and Singapore, are also active in investing outside their countries. In particular, the Malaysian multinationals are establishing large-scale oil palm plantations in Indonesia. The Malaysian palm oil-based multinationals, which are defined as POB MNCs, need to invest in Indonesia as they are facing limited suitable lands to plant oil palms domestically. They also have to rely on immigrants labour for their Malaysian oil palm plantations. As a result, the POB MNCs’ costs of palm oil production in Malaysia are higher as compared to the costs in Indonesia. The POB MNCs’ operations in Indonesia will have a major impact on their long-term business viability as their Malaysian oil palm operations would continue to incur higher production costs. The palm oil industry is important to the Malaysian economy. Thus, the POB MNCs need to be supported by the Malaysian government to develop competitive advantages to operate successfully in Malaysia and Indonesia. The competitive advantages of the POB MNCs have been their superior oil palm plantation management techniques and skilled estate managers, both of which had been accumulated over decades. This study examines the role of network relationships in the Malaysian palm oil industry, and how the network relationships contribute to firm competitive advantages of the POB MNCs. A qualitative research method was used to gather primary data on network relationships by interviewing a sample of informants…